The roles of cytosolic and membrane-bound carbonic anhydrase in acid-base regulation in rainbow trout, Oncorhynchus mykiss - Georgalis, Tina Lito (University of Ottawa (Canada), 2005)
Carbonic anhydrase (CA) is an important enzyme that catalyzes the reversible hydration/dehydration reactions of CO2. In mammals, there are at least 15 isoforms of CA with diverse tissue distributions, widely varying kinetic properties and numerous physiological functions. The research reported in this thesis focused on the molecular characterization and physiological roles of two rainbow trout (Oncorhynchus mykiss) CA isoforms, the membrane-associated CAIV and a cytosolic form (tCAc). More specifically, I evaluated the roles of CAIV and tCAc in renal acidification and bicarbonate reabsorption at rest and during respiratory acidosis. In addition, the localization of these proteins within the kidney and gill was investigated, and the role of tCAc in branchial acid-base regulation was assessed. Using an array of techniques that included Northern analysis, Western analysis, real time RT-PCR, immunohistochemistry and in situ hybridization, I demonstrated that trout CAIV is specifically localized to renal tubule cells, whereas tCAc is widely distributed across different tissues such as gill, kidney and brain. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.